Balance and Challenges to Inclusion in the Light of Pandemic: Cues and Pillars for High Quality Alliances Building - Baruzzo, Sara; Tiozzo Brasiola, Oscar (Formazione & insegnamento, 2022)
In January 2020 the World Health Organization declared Covid-19 a public health Emergency of international concern. Since then, no remark about school or about the birth of coalitions and «Community Agreement» can leave out of consideration this event or its consequences. In contemporary modern society, in which complexity is directly reflected in heterogeneity of classrooms, if it is true that talent doesn’t make the difference because «it is not a gift» (Margiotta, 2018), it’s necessary to focus on some conditions that cannot be omitted and to rethink in generative terms didactics and alliances building and give everybody the same opportunities. Every day teachers face balance challenges and tightrope walkings like acrobats, like craftsmen who, absorbed in the dynamics of «risk-society» (Beck, Giddens, 1980), tries to create practical models of inclusion. Walking the tightrope becomes the perfect metaphor for a good-quality teaching and alliances building that tries to give, in real and digital setting, proper answers to people full of capabilities. It is worth it to benefit from all these changes and press against all those values, tools and main «pillars» (2030 Agenda) that let us think, plan and create inclusive settings with the right equipment to give each student the opportunity to show what he is interested in and cultivate his own interests.